Examination of early treatment effects and related biases during the conduct of two UK- wide pragmatic orthopaedic surgical trials: ProFHER and UK FROST. (2023) - Knowlson, C. N.; Brealey, S.; Keding, A.; Torgerson, D.; Rangan, A.
No abstract available